The heart of the matter: modeling HIV-associated cardiovascular comorbidities in nonhuman primate models - Khurana, Vansh; Radu, Rodica; Feinstein, Matthew J.; Apetrei, Cristian; Pandrea, Ivona (Frontiers in Cellular and Infection Microbiology, 2025)
With the advent of antiretroviral therapy (ART) that effectively suppresses HIV replication, and reduced AIDS progression, the clinical spectrum of HIV infection has dramatically changed. Currently, the people living with HIV (PLWH) who receive ART have a nearly normal prognostic of survival, yet they still experience higher morbidity and mortality than age-matched uninfected subjects. The higher risk of death in PLWH is linked to persistence of residual systemic inflammation and T-cell activation. These factors contribute to accelerated aging and higher incidence of HIV-associated non-AIDS conditions, thereby presenting new diagnostic and therapeutic challenges. This new shifting paradigm of HIV infection associates a higher incidence of cardiovascular disease (CVD), such as stroke, acute myocardial infarction and sudden cardiac death, in stark contrast to the reduced incidence of opportunistic infections. The incidence of acute myocardial infarction and coronary disease is several folds higher in PLWH than in the general population. Study of United States (US) death certificates listing HIV infection shows that the deaths from CVD doubled between 1996 and 2006. CVD will become an even more prominent comorbidity considering that more than 50% of PLWH in the US are over 50 years old, an age that more frequently associates CVD, and cardiovascular complications are more frequent in urban African-Americans and Hispanics, which are disproportionately affected by HIV. Therefore, reducing the overall risk of these complications will become the primary challenge in the management of chronic HIV infection. Not surprisingly, the REPRIEVE trial showed a substantial benefit of statins to PLWH, and the current guidelines include statin administration to PLWH. Nonhuman primate (NHP) models for the cardiovascular comorbidities associated with HIV are currently available and their use for testing new therapeutic approaches aimed at countering the effects of hypercoagulability and CVD is discussed. Their use can be of tremendous help to understand the etiology, pathophysiology, and the determinants of CVD in PLWH, which are currently poorly understood. Use of the NHP models could help in dissecting the relative contribution of the virus, behavioral factors, and ART to cardiovascular risk, having the potential to help us establish new strategic approaches aimed at controlling HIV-related CVD.